2006
DOI: 10.1179/146532806x120372
|View full text |Cite
|
Sign up to set email alerts
|

Maternal blood aspiration: an unusual cause of respiratory distress in a neonate

Abstract: Maternal blood aspiration is an unusual cause of respiratory distress in neonates. It is occasionally seen in babies born to mothers with antepartum haemorrhage (APH). We report a term neonate with a history of maternal APH who developed respiratory distress soon after birth with a radiological appearance compatible with aspiration syndrome. The infant required ventilation for 36 hours. The aspirated blood was the mother's.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The early onset of respiratory distress, which lasted less than a week seen in our case is similar to other reported cases of respiratory distress following maternal blood aspiration. [2,[8][9][10] Our findings add to that of Saia et al, who reported a case of a newborn with MOD consisting of respiratory failure, hyperbilirubinemia, and renal dysfunction. [8] Intrauterine distress can be associated with fetal gasping and aspiration of maternal blood, and with hypoxemic injury to other organs.…”
Section: Discussionsupporting
confidence: 86%
“…The early onset of respiratory distress, which lasted less than a week seen in our case is similar to other reported cases of respiratory distress following maternal blood aspiration. [2,[8][9][10] Our findings add to that of Saia et al, who reported a case of a newborn with MOD consisting of respiratory failure, hyperbilirubinemia, and renal dysfunction. [8] Intrauterine distress can be associated with fetal gasping and aspiration of maternal blood, and with hypoxemic injury to other organs.…”
Section: Discussionsupporting
confidence: 86%